Diagnostic Value of GGT/PLT, AST/ALT, and AST/PLT Ratios in Intrahepatic Cholestasis of Pregnancy: A Retrospective Analysis - Ayas Ozkan, Merve; Dayanan, Ruken; Karabay, Gulsan; Vanli Tonyali, Nazan; Duygulu Bulan, Dilara; Seyhanli, Zeynep; Akin, Furkan; Caglar, Ali Turhan (Gynecology Obstetrics & Reproductive Medicine, 2025)
OBJECTIVES: This study evaluated the diagnostic performance of gamma-glutamyltransferase-to-platelet (GGT/PLT), aspartate aminotransferase-to-alanine aminotransferase (AST/ALT), and aspartate aminotransferase-to-platelet (AST/PLT) ratios in intrahepatic cholestasis of pregnancy (ICP), and their association with composite adverse perinatal outcomes (CAPO). STUDY DESIGN: A retrospective cohort analysis was conducted of 329 pregnant women (156 with ICP, 173 controls) who delivered at a tertiary center between November 2022 and November 2024. ICP was diagnosed in the presence of pruritus and fasting serum bile acid levels ≥10 μmol/L. Maternal demographics, liver enzymes, platelet counts, and perinatal outcomes were retrieved from hospital records. Ratios were calculated from second-trimester laboratory results. Diagnostic performance was evaluated using receiver operating characteristic (ROC) analysis. CAPO was defined as at least one of the following: preterm birth, fetal growth restriction, oligohydramnios/polyhydramnios, premature rupture of membranes, or intrapartum fetal distress. RESULTS: Compared with controls, the ICP group had higher GGT/PLT (0.05 [0.07] vs. 0.04 [0.07], p<0.001) and AST/PLT ratios (0.19 [0.30] vs. 0.07 [0.04], p<0.001), and a lower AST/ALT ratio (0.76 [0.55] vs. 1.09 [0.91], p<0.001). Among the ratios, AST/PLT provided the highest diagnostic accuracy for distinguishing ICP (AUC=0.840; cut-off >0.083; sensitivity 77.3%; specificity 74.8%), followed by AST/ALT (AUC=0.788; cut-off <1.060; sensitivity 75.6%; specificity 75.0%), with GGT/PLT showing the lowest diagnostic value (AUC=0.668; cut-off >0.044; sensitivity 67.5%; specificity 64.1%). The ICP group had increased rates of preterm birth (33.3% vs. 10.8%, p<0.001), NICU admission (22.4% vs. 10.4%, p=0.003), and CAPO (50.0% vs. 13.9%, p<0.001), but none of the assessed ratios were significantly associated with CAPO in ICP cases. CONCLUSIONS: Among the indices evaluated, AST/ALT and AST/PLT ratios showed moderate-to-good accuracy in diagnosing ICP, while the GGT/PLT ratio exhibited moderate accuracy. These indices can be useful, cost-effective, and accessible adjunctive tools for ICP diagnosis, particularly in settings where bile acid testing is unavailable. However, their ability to predict perinatal outcomes is limited.